2014
DOI: 10.1093/nar/gku395
|View full text |Cite
|
Sign up to set email alerts
|

SEPPA 2.0—more refined server to predict spatial epitope considering species of immune host and subcellular localization of protein antigen

Abstract: Spatial Epitope Prediction server for Protein Antigens (SEPPA) has received lots of feedback since being published in 2009. In this improved version, relative ASA preference of unit patch and consolidated amino acid index were added as further classification parameters in addition to unit-triangle propensity and clustering coefficient which were previously reported. Then logistic regression model was adopted instead of the previous simple additive one. Most importantly, subcellular localization of protein anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 18 publications
1
52
0
Order By: Relevance
“…We selected four conformational and four linear epitope predictors as our base learners. The conformational predictors were DiscoTope 2.0 [9], ElliPro [10], SEPPA 2.0 [11], and Bpredictor [18], and the linear epitope predictors were BepiPred [5], ABCpred [6], AAP [7], and BCPREDS [8]. We calculated the Pearson’s correlation coefficients for the prediction scores produced by the base prediction tools.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We selected four conformational and four linear epitope predictors as our base learners. The conformational predictors were DiscoTope 2.0 [9], ElliPro [10], SEPPA 2.0 [11], and Bpredictor [18], and the linear epitope predictors were BepiPred [5], ABCpred [6], AAP [7], and BCPREDS [8]. We calculated the Pearson’s correlation coefficients for the prediction scores produced by the base prediction tools.…”
Section: Resultsmentioning
confidence: 99%
“…We conducted the experiments on several representative epitope predictors released in 2008–2014: SEPPA 2.0 (2014), DiscoTope 2.0 (2012), Bpredictor (2011), CBTOPE (2010), and ElliPro (2008). Each of them had been trained and tested by different data sets [911,18,24]. In each experiment, we selected one epitope predictor for comparison.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three web servers SEPPA [52], Epitopia [49], and EPCES [53] were published in 2009. SEPPA employs two concepts, "unit patch of residue triangle" and "clustering coefficient" to describe the local spatial context and spatial compactness, and combines them to predict epitopes.…”
Section: B-cell Epitopesmentioning
confidence: 99%
“…Number of methods that utilize 3D structure of antigens for discontinuous epitope prediction have also been developed. These methods use different approaches for prediction such as solvent accessibility of surface residues [123,124], solvent accessibility with propensity scores [125], and propensity scores with packing density of amino acids [126]. An account of major tools/servers that are involved in conformational epitope prediction is provided in Studies have shown that the analysis of antigen-antibody complex structures is very useful for the characterization of conformational epitopes [134].…”
Section: Computational Prediction Of Allergen Epitopesmentioning
confidence: 99%